Dynamics of Prochlorococcus and Synechococcus at Station ALOHA Revealed through Flow Cytometry and High-Resolution Vertical Sampling - van den Engh, Ger J.; Doggett, Joseph K.; Thompson, Anne W.; Doblin, Martina A.; Gimpel, Carla N. G.; Karl, David M. (Frontiers in Marine Science, 2017)
The fluorescence and scattering properties of Prochlorococcus and Synechococcus at Station ALOHA as measured by flow cytometry (termed the FCM phenotype) vary with depth and over a variety of time scales. The variation in FCM phenotypes may reflect population selection or physiological acclimation to local conditions. Observations before, during, and after a storm with deep water mixing show a short-term homogenization of the FCM phenotypes with depth, followed by a return to the stable pattern over the time span of a few days. These dynamics indicate that, within the upper mixed-layer, the FCM phenotype distribution represents acclimation to ambient light. The populations in the pycnocline (around 100 m and below), remain stable and are invariant with light conditions. In samples where both cyanobacteria coexist, fluorescence properties of Prochlorococcus and Synechococcus are tightly correlated providing further evidence that FCM phenotype variability is caused by a common environmental factor or factors. Measurements of the dynamics of FCM phenotypes provide insights into phytoplankton physiology and adaptation. Alternatively, FCM phenotype census of a water mass may provide information about its origin and illumination history.